Case Report Penile Fracture With Corpus Cavernosum Rupture Without Urethral Disruption Due to Sexual Intercourse - Pratama, Dio Rancha; Taher, Taufik Rakhman; Jouwena, Davis Roland Gustav (Jurnal Health Sains, 2023)
Objective: We reported a case of penile fracture with unilateral corpus cavernosum rupture that underwent penile exploration and reconstruction measures. Case presentation: We reported a 45-year-old male patient complaining of penile pain, swelling, loss of erectile ability and a "pop" sound after bumping during sexual intercourse. The patient can still urinate. Physical examination found a swollen penis, hematom, eggplant-like deformity, and angulation to the right accompanied by tenderness. Routine blood support examination within normal limits. Based on data obtained from the anamnesis, physical examination, diagnosis of penile fracture was established and the patient was treated with exploration and reconstruction of the penis <24 hours. Discussion: Patients carried out exploratory actions carried out with circumferential and degloving subcoronal incisions, 4 cc blood clots were evacuated and ruptures were seen in the tunica albuginea corpus cavernosum sinistra along 4 cm. Reconstruction is carried out with primary sutures on the torn corpus cavernosum. The patient is carried out treatment for 5 days. At the postoperative 7-day evaluation, the surgical wound was good and urination was good. At the evaluation of 1 month the patient can have a painless erection with an erection hardness score of 4, there is no penile deformity. Conclusion: Penile fracture is a urological emergency that shows a good prognosis if you get surgical intervention immediately (<24 hours) and can reduce the number of complications